2x+ 1 = 3x - 1 ;
1 + 1 = 3x - 2x ;
2 = x ;
x = 2 ;
Then, y = 2x2 + 1 = 5 ;
<u>Answer:</u>
2(-5 - 7j) = -10 - 14j
<u>Step-by-step explanation:</u>
Using the distributive property means that we have to multiply both -5 and -7j by 2:
2(-5 - 7j)
⇒ 2 × -5 + 2 × -7j
⇒ -10 - 14j
Answer:
32
Step-by-step explanation:
You use angle chasing. Since a triangle's angle has to add up to 180, the other angle is 180-79-69. This gives 32. So angle E is 32 degrees. Since they are parallel, that means that E equals to D. That means that D is 32, so 32 is now the answer.
HAPPY NOW BRAINLY? I JUST DIDN'T ADD AN EXPLANATION ON THE OTHER ONE AND YOU DELETED IT! I GOT BRAINLIEST! HE STILL GOT THE ANSWER ANYWAYS.
Answer:
the possible outcome are two but don't trust me on that
Answer:
D. 21.
Step-by-step explanation:
The general form of the equation of a circle is:
(x - a)^2 + (y - b)^2 = r^2 where r is the radius.
Comparing:
(x + 5)^2 + (y + 7)^2 = 21^2
So r^2 = 21^2
making r = √21^2
= 21.
plz make me brainliest